BETWEEN A POLE AND A MAN. STANISŁAW BRZOZOWSKI’S AND STEFAN ŻEROMSKI’S LITERARY STRATEGIES - Badowska, Katarzyna (Prace Polonistyczne, 2019)
The author analyzes the strategies of keeping balance between the characters’ subjectivity and their national identity in the novels written by Stefan Żeromski and Stanislaw Brzozowski shortly before Poland regained independence. She argues that Żeromski, although well known for creating characters who are patriotic, committed, and actively involved in the making of their country’s history, tried to distance himself from the so-defined Polishness in order to show more universal characters. All Brzozowski’s works, on the other hand, prioritized the concept of a universal human being over an individual defined solely in terms of his Polish national identity, and asked whether a contemporary human being has any homeland at all. At the end of his life, however, he re-embraced his Polish identity, gradually giving up on the concept of a “universal man.”